1984
DOI: 10.1128/iai.46.3.831-834.1984
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by sugars of Candida albicans adherence to human buccal mucosal cells and corneocytes in vitro

Abstract: The adherence and inhibition of adherence of Candida albicans to epithelial cells was studied for human cells obtained from skin (corneocytes) and buccal mucosa. The yeast adhered to both kinds of cells, although in somewhat greater numbers to buccal mucosal cells. Adherence to the cells of different individuals was variable, but the ratios of values for the two kinds of cells from a single subject were quite constant. Inhibition of adherence was produced by several sugars, including the aminosugars mannosamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 10 publications
3
20
0
Order By: Relevance
“…There is evidence to suggest that Candida albicans can adhere differently on different biological substrates. Buccal cells prove to be a better target tissue than corneocytes for a foothold for Candida [16,21]. Our experiment suggests that the inner face of the superficial layers of the stratum corneum of diabetics could be more prone to Candida invasion than that of non-diabetic persons.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…There is evidence to suggest that Candida albicans can adhere differently on different biological substrates. Buccal cells prove to be a better target tissue than corneocytes for a foothold for Candida [16,21]. Our experiment suggests that the inner face of the superficial layers of the stratum corneum of diabetics could be more prone to Candida invasion than that of non-diabetic persons.…”
Section: Discussionmentioning
confidence: 64%
“…We present in this paper evidence proving that Candida albicans can grow on the same cornified substrate. Such observations could in part be related to the adhesion properties of Candida to comeocytes [16,17]. Studies of adherence of Candida to exfoliated epithelial cells in vitro are severely limited by technical considerations [18].…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides and adhesins present in C. albicans cell wall mediate many of the adhesion processes of the yeast [36]. Initial research indicated that the addition of galactose or galactosamine reduced C. albicans attachment to buccal mucosal cells in vitro [37]. However, this is in contrast to a study in which the pre-treatment of C. albicans with galactose failed to inhibit adherence [38].…”
Section: Fluorescence Imagingmentioning
confidence: 93%
“…The terminal sugars of the host cell surface glycoproteins have been shown to interact with receptors on candidal cell walls (Critchley and Douglas, 1987b), being inhibited by sugars such as r.-fucose. N-acetylgluc?samine, mannosamine, glucosamine and galactosamine (Collins-Lech et al, 1984;Critchley and Douglas, 1987b). Also, a number of putative adhesins of C. albicans have been studied including cell wall chitin (Segal et al, 1982;Lehrer et al, 1988) lipids (Ghannoum et al, 1986), complement receptors (Gilmore et al, 1987;Alaei et al, 199~), fibronectin adhesins (Klotz et al, 1994), mannan (Sandin, 1987;Miyakawa et al, 1992), proteins (Calderone and ScheId, 1987;Critchley and Douglas, 1987a), and mannoproteins (Tosh and Douglas, 1992;I,?bert-Bernard et .al, 1995).…”
Section: Adherencementioning
confidence: 99%